We're going on a bear hunt - Rosen, Michael 1946- (Walker Books, 1997)
Have you ever gone on a bear hunt? Come along on this one with a brave young family -- four children (including the baby) and their father. They're not scared. With them you will cross a field of tall, wavy grass ("Swishy swashy!"), wade through a deep, cold river ("Splash splosh!"), struggle through swampy mud ("Squelch squerch!"), find your way through a big, dark forest ("Stumble trip!"), fight through a whirling snowstorm ("Hoooo woooo!"), and enter a narrow, gloomy cave. WHAT'S THAT? You'll soon learn just what to do to escape from a big, furry bear! With tremendous pace, humor, and verve, Michael Rosen has retold a favorite tractional story. The pictures by Helen Oxenbury, one of the most widely loved contemporary artists, are full of masterly characterizations, delightful comedy, and high drama, set in lovely sweeping landscapes. This is a book not to be missed, one to be chanted aloud and acted out, to be enjoyed over and over again. It is a picture book on the grand scale.